Rabindranath Tagore: a selected short stories - Quayum, Mohammad Abdul (Macmillan, 2011)
Throughout his life and career, Rabindranath Tagore (1861-1941), Asia’s first Nobel Laureate (1913), and the most gifted and insightful writer of his time, once hailed as ‘the greatest star shinning in the eastern sky’, remained an ardent advocate of peace, justice and human fraternity. A champion of the spiritual one-identity of humanity, he sought to bring the human race in one nest, overcoming the differences that breed exclusivism, antagonism, prejudice, hatred and violence in society. In a tribute to this iconic Renaissance figure, Bertrand Russell wrote, ‘[Tagore] has contributed… much… to the most important work of our time, namely, the promotion of understanding between races… [and] on this account he is worthy of the highest honour.’ In a similar vein, Einstein commented, ‘[Tagore] served mankind… spreading everywhere a gentle and a free thought in a manner such as the Seers… have proclaimed as the ideal.’